Processor for impulsive noise suppression in telecommunication channels - Csaba Stupak; Rastislav Lukac; Stanislav Marchevsky (Communications - Scientific letters of the University of Zilina, 2000)
In recent years, many linear filters have been replaced by nonlinear filters, especially in case of impulse noise distorting. Stack filters, the class of non-linear filters are very interesting for easy hardware realisation and threshold decomposition property. The development of digital HDTV gives technological push in this area. Various of very efficient order-statistics filters such as median or LUM smoother are useful in many applications. In addition, these filters can be realised as stack filters. This paper gives a short review of the stack filter class.